Britain and Germany imagining the future of Europe : national identity, mass media and the public sphere - Novy, Leonard (Palgrave Macmillan, 2013)
"Recounting the gripping tale of Europe's quest for a constitution surveying events from Joschka Fischer's ground-breaking Quo-Vadis speech at Berlin's Humboldt University in 2000, to the failed referendums in France and the Netherlands fiver years later, this book addresses a relatively new aspect in EU Studies: the importance of public communication for bridging the legitimacy dilemmas of European integration. Through analysis of newspaper coverage on the debate over the future of Europe in Great Britain and Germany between 2000 and 2005, this book explores how national identities interact with, and are reproduced in, the discursive construction of the future of the EU and in doing so, it provides powerful insights into Europe's emerging communicative space(s). The results of the three case studies suggest that the debate surrounding the future of Europe touch the core of a European construction, which exposes contradictory connotations and expectations while also highlighting that totally different ontological assumptions exist in Germany and the UK. The implications for the "European Public Sphere' are severe as while communication across borders does not require consensus, it presupposes a common understanding of the issues at stake"..